A theorem of the Phragmén-Lindelöf type for solutions of an evolution equation of the second order with respect to time variable - Antypko, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We consider a solution u(x, t) of the general linear evolution equation of the second order with respect to time variable given on the ball Π(T) = (x,t): xε R n, t ε [0, T] and study the dependence of the behavior of this solution on the behavior of the functions at infinity.